Cancer incidence and mortality in Australia from 2020 to 2044 and an exploratory analysis of the potential effect of treatment delays during the COVID-19 pandemic: a statistical modelling study. (June 2022) - Luo, Qingwei; O'Connell, Dianne L; Yu, Xue Qin; Kahn, Clare; Caruana, Michael; Pesola, Francesca; Sasieni, Peter; Grogan, Paul B; Aranda, Sanchia; Cabasag, Citadel J; Soerjomataram, Isabelle; Steinberg, Julia; et al.
Summary: Background: Long-term projections of cancer incidence and mortality estimate the future burden of cancer in a population, and can be of great use in informing the planning of health services and the management of resources. We aimed to estimate incidence and mortality rates and numbers of new cases and deaths up until 2044 for all cancers combined and for 21 individual cancer types in Australia. We also illustrate the potential effect of treatment delays due to the COVID-19 pandemic on future colorectal cancer mortality rates. Methods: In this statistical modelling study, cancer incidence and mortality rates in Australia from 2020 to 2044 were projected based on data up to 2017 and 2019, respectively. Cigarette smoking exposure (1945–2019), participation rates in the breast cancer screening programme (1996–2019), and prostate-specific antigen testing rates (1994–2020) were included where relevant. The baseline projection model using an age-period-cohort model or generalised linear model for each cancer type was selected based on model fit statistics and validation with pre-COVID-19 observed data. To assess the impact of treatment delays during the COVID-19 pandemic on colorectal cancer mortality, we obtained data on incidence, survival, prevalence, and cancer treatment for colorectal cancer from different authorities. The relative risks of death due to system-caused treatment delays were derived from a published systematic review. Numbers of excess colorectal cancer deaths were estimated using the relative risk of death per week of treatment delay and different durations of delay under a number of hypothetical scenarios. Findings: Projections indicate that in the absence of the COVID-19 pandemic effects, the age-standardised incidence rate for all cancers combined for males would decline over 2020–44, and for females the incidence rate would be relatively stable in Australia. The mortality rates for all cancers combined for both males and females are expected to continuously decline during 2020–44. The total number of new cases are projected to increase by 47·4% (95% uncertainty interval [UI] 35·2–61·3) for males, from 380 306 in 2015–19 to 560 744 (95% UI 514 244–613 356) in 2040–44, and by 54·4% (95% UI 40·2–70·5) for females, from 313 263 in 2015–19 to 483 527 (95% UI 439 069–534 090) in 2040–44. The number of cancer deaths are projected to increase by 36·4% (95% UI 15·3–63·9) for males, from 132 440 in 2015–19 to 180 663 (95% UI 152 719–217 126) in 2040–44, and by 36·6% (95% UI 15·8–64·1) for females, from 102 103 in 2015–19 to 139 482 (95% UI 118 186–167 527) in 2040–44, due to population ageing and growth. The example COVID-19 pandemic scenario of a 6-month health-care system disruption with 16-week treatment delays for colorectal cancer patients could result in 460 (95% UI 338–595) additional deaths and 437 (95% UI 314–570) deaths occurring earlier than expected in 2020–44. Interpretation: These projections can inform health service planning for cancer care and treatment in Australia. Despite the continuous decline in cancer mortality rates, and the decline or plateau in incidence rates, our projections suggest an overall 51% increase in the number of new cancer cases and a 36% increase in the number of cancer deaths over the 25-year projection period. This means that continued efforts to increase screening uptake and to control risk factors, including smoking exposure, obesity, physical inactivity, alcohol use, and infections, must remain public health priorities. Funding: Partly funded by Cancer Council Australia.